Immunological and hemato-biochemical effects on catfish (Clarias gariepinus) exposed to dexamethasone - Sayed, Alaa El-Din H.; Taher, Hesham; Soliman, Hamdy A. M.; Salah El-Din, Alaa El-Din (Frontiers in Physiology, 2022)
Dexamethasone (glucocorticoid) was recently shown to be a life-saving drug for the treatment of SARS-CoV-2 disease. Water and sediments can be contaminated by sewage treatment plants when this product is widely used. Accordingly, we evaluated the effects of dexamethasone as pharmaceutical residue on Clarias gariepinus following exposure and post-exposure recovery on blood biochemical, antioxidant, and cytokine markers. Three experimental groups were examined. Control, fish exposed to 0.3 mg/L of dexamethasone, and fish exposed to 3 mg/L of dexamethasone for 7 days followed by a15-day recovery period. Hematological indices, such as red blood cell number, hemoglobin (Hb), platelets, mean corpuscular hemoglobin concentration, and large lymphocytes, were significantly declined following exposure to dexamethasone compared to control. In contrast, hematocrit (Ht), mean corpuscular volume, monocytes, small lymphocytes, and mean corpuscular hemoglobin increased significantly depending on the dose-concentration. Liver and kidney function, other biochemical parameters (albumin and globulin), cortisol and cytokine (IL-1β and IL-6) concentrations increased significantly after exposure to dexamethasone compared to control. Antioxidants and acetylcholinesterase enzymes were significantly decreased in catfish treated with dexamethasone cumulatively with doses. After a recovery period, blood biochemical, antioxidant, and cytokine markers were still elevated compared with the control group. In conclusion, dexamethasone at concentrations present in water bodies causes deleterious effects on blood biomarkers, biochemical and antioxidant as well as immune up-regulation in catfish till after depuration period.